2022
DOI: 10.3892/etm.2022.11725
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiles of tRNA‑derived fragments in high glucose‑treated tubular epithelial cells

Abstract: Transfer RNA-derived fragments (tRFs), a novel class of small non-coding RNA produced by the cleavage of pre-and mature tRNAs, are involved in various diseases. Renal tubulointerstitial fibrosis is a common final pathway in diabetic nephropathy (DN) in which hyperglycemia-induced tubular extracellular matrix (ECM) accumulation serves a vital role. The present study aimed to detect and investigate the role of tRFs in the accumulation of tubular ECM. Differentially expressed tRFs were analysed with high-throughp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 64 publications
(66 reference statements)
1
2
0
Order By: Relevance
“…Our high-throughput sequencing results also showed the involvement of various types of tRFs, with tRF-5s accounting for the highest proportion. This result was similar to the sequencing result for HG-treated renal tubular epithelial cells observed in our previous study [ 20 ]. It is hypothesized that tRF-5s play a particularly important role in DKD, and this supposition needs to be tested via further study in the future.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our high-throughput sequencing results also showed the involvement of various types of tRFs, with tRF-5s accounting for the highest proportion. This result was similar to the sequencing result for HG-treated renal tubular epithelial cells observed in our previous study [ 20 ]. It is hypothesized that tRF-5s play a particularly important role in DKD, and this supposition needs to be tested via further study in the future.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies by our team showed that tRFs affect podocyte differentiation and podocyte injury in patients with idiopathic nephrotic syndrome [ 18 , 19 ]. The expression profiles of renal tubular epithelial cells induced by high glucose (HG) were also explored [ 20 ]. Thus, these previous studies initially demonstrated the promising clinical applications of tRFs.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, a similar decrease in tRF-1:30-Gln-CTG-4 expression was also observed in the serum of patients with DN. Intriguingly, the researchers found that overexpressing tRF-1:30-Gln-CTG-4 in renal tubular epithelial cells led to a reduction in extracellular matrix deposition induced by HG, suggesting a potential protective role [ 98 ]. In a subsequent phase of their investigation, the researcher examined diabetic patients with and without albuminuria, identifying six differentially expressed tsRNAs (tRF5-GluCTC, tRF5-AlaCGC, tRF5-ValCAC, tRF5-GlyCCC, tRF3-GlyGCC, and tRF3-IleAAT) [ 99 ].…”
Section: Tsrnas In Renal Diseasesmentioning
confidence: 99%